Strategi Getok Tular dalam Public Relations Islami: Studi Komunikasi Berbasis Komunitas Jamaah Umrah Uskinu Ponorogo - Achmad Arfinanto Arsyadani; Luhur Prasetiyo (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study explores the word of mouth (WOM) strategy within the framework of Islamic public relations as implemented by Uskinu Ponorogo, a religious travel agency specializing in Umrah services. The research is motivated by the increasing reliance on personal recommendations amid widespread fraud cases in the Umrah travel sector, and the lack of scholarly attention to WOM communication embedded in Islamic values. Using a qualitative approach with a field research design, data were collected through an in-depth interview with the agency’s public relations officer. The findings reveal that interpersonal communication among former pilgrims, facilitated through regular alumni gatherings, plays a key role in building public trust and strengthening loyalty by leveraging both religious legitimacy and institutional credibility. This community-based and spiritually grounded WOM strategy has proven to be an effective, ethical, and sustainable communication tool for enhancing the agency’s public reputation. The study contributes theoretically to the discourse on Islamic public relations and provides practical insights for faith-based service institutions.